Changes in Rest-Activity Rhythms in Adolescents as They Age: Associations With Brain and Behavioral Changes in the ABCD Study - Zhang, Rui; Schwandt, Melanie L.; Vines, Leah; Volkow, Nora D. (Journal of the American Academy of Child and Adolescent Psychiatry, 2025)
Adolescents with disrupted rest-activity rhythms (RARs), including shorter sleep duration, later sleep timing, and low physical activity levels, are at greater risk for mental health and behavioral problems. It remains unclear whether the same associations can be observed for within-subject changes in RARs. This longitudinal investigation on RARs used Fitbit data from the Adolescent Brain Cognitive Development (ABCD) Study at the 2-year follow-up (FL2) (ages 10-13 years) and 4-year follow-up (FL4) (ages 13-16 years). Good-quality Fitbit data were available for 963 youths at both time points. Changes in RARs from FL2 to FL4, their environmental and demographic contributors, and brain and behavioral correlates were examined. From FL2 to FL4, adolescents showed decreases in sleep duration and physical activity as well as delayed sleep timing (Cohen d = 0.44-0.75). Contributions of environmental and demographic factors to RAR changes were greatest for sleep timing (explained 10% variance) and least for sleep duration (explained 1% variance). Delays in sleep timing had stronger correlations with behavioral problems including impulsivity and poor academic performance than reductions in sleep duration or physical activity. Additionally, the various brain measures differed in their sensitivity to RAR changes. Reductions in sleep duration were associated with decreased functional connectivity between subcortical regions and sensorimotor and cingulo-opercular networks and with enhanced functional connectivity between sensorimotor, visual, and auditory networks. Delays in sleep timing were mainly associated with gray matter changes in subcortical regions. The current findings corroborate the importance of sleep and physical activity in brain neurodevelopment and behavioral problems in adolescents. RARs might serve as biomarkers for monitoring behavioral problems and be potential therapeutic targets for mental disorders in adolescents. Using data from the Adolescent Brain Cognitive Development (ABCD) Study, the authors identified associations between rest-activity rhythms such as sleep timing, sleep duration, physical activity, and behavioral/brain changes in adolescents. Delays in sleep timing showed a higher correlation than reductions in sleep duration or physical activity with behavioral problems including impulsivity and poor academic performance. Structural and functional brain changes were observed with changes in sleep timing and duration. Environmental factors such as school involvement and time of the year influenced changes in sleep and activity.